The Effects of Bevacizumab in Augmenting Trabeculectomy for Glaucoma : Systematic Review and Meta-Analysis: Poster Presentation - Observational Study - Resident - Rusli, Richardo; Kasih, Franky Richard (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Anti-vascular endothelial growth factor (VEGF) agents have been used to slow the healing response and postoperative scar tissue formation. To determine the effectiveness of adding Anti VEGF bevacizumab to the results of trabeculectomy in glaucoma. Methods : Searches were conducted in a structured way using keywords across several data sources, including Pubmed, Proquest and Cochrane library. The keywords used for searching were “Bevacizumab”, “Trabeculectomy” and “Glaucoma”. The reviewed articles are Randomized Control Trial in english, conducted on humans in the last 15 years. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results : From a total of 353 articles, there were 6 studies with 362 eyes of 352 patients been evaluated for the effectiveness of bevacizumab addition to trabeculectomy. The primary outcome of all articles was the assessment of Intra Ocular Pressure (IOP). No significant difference in IOP was found between the subconjunctival bevacizumab + Mytomycin-c group and mytomycin-c alone group (MD 0.11 ; 95% CI -0.10 to 0.33), as well as subconjunctival comparison with mytomycin-c (MD 0.11 ; 95% CI -0.29 to 0.50). Similar results were also found in the intracameral and placebo groups (MD 0.08 ; -0.22 to 0.38). However, 3 articles reported significant differences in peripheral vascularity of the bleb both by the Moorfields Bleb Grading System and by the Indiana Bleb Appearance System. Conclusion : The addition of bevacizumab to trabeculectomy did not show any benefit in reducing IOP when compared with MMC. But it gives better peripheral vascularity of the bleb.